Stupeni rosta - Lepeshev, V. P. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to show the contemporary state in the perspectives of development in the most remote higher educational institution of physical culture in Russia, the Khabarovsk state institute of physical culture.